Refeeding Syndrome in Critically Ill Patients: An Integrative Review on Diagnostic Complexity and the Applicability of Cautious Protocols - Santos, Artur Valdez dos; Valdez, Karolline Kamilla Oliveira Tavares; Pombeiro, Gilson Augusto Nunes Martins (Revista JRG de Estudos Acadêmicos, 2025)
Refeeding Syndrome (RS) is a severe metabolic complication that mostly occurs in malnourished patients after the initiation of nutritional support. This integrative review aimed to synthesize evidence on risk factors, diagnostic criteria controversy and management of adults and elderly in the setting of intensive care units (ICUs). Results showed a large variability of incidence of RS due to the lack of universal definition and divergence between purely electrolytic criteria and those requiring clinical features. Hypophosphatemia is the hallmark of RS, and risk factors include low BMI, severe weight loss, low caloric intake and pre-existing electrolyte disturbances. Management includes mandatorily initial caloric restriction (5 to 10 Kcal/Kg/day for high risk patients) and gradual progression of the diet. Prophylactic thiamine supplementation and daily monitoring of electrolytes in the first 72 hours are essential.